5lnx-4=7

Simple and best practice solution for 5lnx-4=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5lnx-4=7 equation:


Simplifying
5lnx + -4 = 7

Reorder the terms:
-4 + 5lnx = 7

Solving
-4 + 5lnx = 7

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 5lnx = 7 + 4

Combine like terms: -4 + 4 = 0
0 + 5lnx = 7 + 4
5lnx = 7 + 4

Combine like terms: 7 + 4 = 11
5lnx = 11

Divide each side by '5nx'.
l = 2.2n-1x-1

Simplifying
l = 2.2n-1x-1

See similar equations:

| -9+20x=16 | | 5=-10n | | r=7r-52.5 | | 3a-(2-9b)= | | 50/950 | | 2m+(9m^2+3m)= | | 3x-17=-17+9x | | 7y-24=-15+6y | | 24y+2x=114 | | 4*x-1=X-2 | | 2(3+3x)-7=17 | | 20x-11-14x=3(2x-5)+4 | | t(t-1)=0 | | 0.5x+5=12.5 | | 4x(4+3y)-9(x+2xy)= | | 5(0.5x+2)=22.5 | | 22.5=10+2.5x | | 35.123/100 | | 5(e^2x)=7 | | 10x+23(x-5)=281 | | 6.5/39 | | (-6/-7)x(-5/3)x4 | | 3(x+7)-4x=12 | | -2(x+7)=6x-38 | | 6.2/0.05 | | (2/-5)(8)(-9/3) | | 5[1/2-x]=5/4 | | 9=0.2x*0.2x*0.6x | | 9=0.2x*0.2x*0.06x | | 8h-4h+2=78 | | 1-7x=7x-1 | | 7x+2=12.5 |

Equations solver categories